Spread of Antigenically Drifted Influenza A(H3N2) Viruses and Vaccine Effectiveness in the United States During the 2018–2019 Season. (30th October 2019) - Flannery, Brendan; Kondor, Rebecca J Garten; Chung, Jessie R; Gaglani, Manjusha; Reis, Michael; Zimmerman, Richard K; Nowalk, Mary Patricia; Jackson, Michael L; Jackson, Lisa A; Monto, Arnold S; Martin, Emily T; Belongia, Edward A; et al.
Abstract: Background: Increased illness due to antigenically drifted A(H3N2) clade 3C.3a influenza viruses prompted concerns about vaccine effectiveness (VE) and vaccine strain selection. We used US virologic surveillance and US Influenza Vaccine Effectiveness (Flu VE) Network data to evaluate consequences of this clade. Methods: Distribution of influenza viruses was described using virologic surveillance data. The Flu VE Network enrolled ambulatory care patients aged ≥6 months with acute respiratory illness at 5 sites. Respiratory specimens were tested for influenza by means of reverse-transcriptase polymerase chain reaction and were sequenced. Using a test-negative design, we estimated VE, comparing the odds of influenza among vaccinated versus unvaccinated participants. Results: During the 2018–2019 influenza season, A(H3N2) clade 3C.3a viruses caused an increasing proportion of influenza cases. Among 2763 Flu VE Network case patients, 1325 (48%) were infected with A(H1N1)pdm09 and 1350 (49%) with A(H3N2); clade 3C.3a accounted for 977 (93%) of 1054 sequenced A(H3N2) viruses. VE was 44% (95% confidence interval, 37%–51%) against A(H1N1)pdm09 and 9% (−4% to 20%) against A(H3N2); VE was 5% (−10% to 19%) against A(H3N2) clade 3C.3a viruses. Conclusions: The predominance of A(H3N2) clade 3C.3a viruses during the latter part of the 2018–2019 season was associated with decreased VE, supporting the A(H3N2) vaccine component update for 2019–2020 northern hemisphere influenza vaccines. Abstract : During the 2018–2019 season in the US, influenza vaccination provided protection against illness due to influenza A(H1N1)pdm09 virus but was not effective against the major clade of A(H3N2) viruses that differed antigenically from the A(H3N2) vaccine component.